The torus one-point diagram in two-dimensional string cosmology - Victor A. Rodriguez (Journal of High Energy Physics, 2023)
Abstract We calculate numerically the torus one-point string diagram in the two-dimensional string cosmology background by decomposing the one-point functions in c = 1 and c = 25 Liouville CFT into torus one-point Virasoro conformal blocks and integrating over the fundamental domain of the torus moduli space. We find a remarkably simple result as a function of the outgoing closed string energy. This torus one-point diagram is expected to contribute to the one-point cosmological wavefunction at order g s , and to the four-point cosmological wavefunction at order g s 2 $$ {g}_s^2 $$ through the disconnected product of the torus one-point diagram and the sphere three-point diagram.